1988
DOI: 10.1159/000146572
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Relative Locations of the Greater Palatine Foramen in Adult Chinese Skulls

Abstract: One hundred dry skulls of adult Chinese of both sexes were studied. They were homogeneous in the form of maxillary arch and having full eruption of the upper third molar, without missing teeth and malposition of teeth. Our findings revealed that the mean distance from the center of the greater palatine foramen (GPF) to the midsagittal plane of the hard palate was 16.00 mm, and to the posterior border of the hard palate, 4.11 mm. The location of the GPF related to the maxillary molars was expressed as percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 13 publications
(27 reference statements)
6
43
4
Order By: Relevance
“…(6,(8)(9)(10)(11)(12)(13)(14) The mean value for this measurement in the present study was in agreement with those of earlier studies on Indian skulls. (8,11) The authors are therefore of the opinion that globally, the foramen might be consistently located 14-15 mm from the mid-palatine raphe.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…(6,(8)(9)(10)(11)(12)(13)(14) The mean value for this measurement in the present study was in agreement with those of earlier studies on Indian skulls. (8,11) The authors are therefore of the opinion that globally, the foramen might be consistently located 14-15 mm from the mid-palatine raphe.…”
Section: Discussionsupporting
confidence: 92%
“…All studies, except that by Wang et al, (12) have consistently found that the GPF is most frequently opposite the third molar (Table VII), (6,8,(10)(11)(12)(14)(15)(16) which would thus seem to be a reliable landmark when attempting to locate the foramen. Nevertheless, there are some differences seen among the various studies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The greater palatine foramen is located medially to the third molar between the second and third molars. [22][23][24] The greater palatine nerve exits the foramen and runs anteriorly, 5 to 15 mm from the gingival border to the incisive foramen. Kravitz and Kusnoto 25 recommended that miniscrews inserted in the palatal slope should be placed mesially to the second molar.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence shows a clear racial variation in the morphometry and relative position of the greater palatine foramen in relation to the maxillary molars among different populations (Wang et al, 1988;Ajmani, 1994;Jaffar & Hamadah, 2003;Methathrathip et al;Saralaya & Nayak, 2007;Chrcanovic & Custódio, 2010). It is also interesting to note that traits such as localization of the facial foramina not only differ between populations of different geographic zones but also within the inhabitants of the same geographic environment (Saralaya & Nayak;Ilayperuma et al, 2009).…”
Section: Introductionmentioning
confidence: 99%